Analysis of Filipino students' science performance in TIMSS 2019 bases for an elementary science learning ecology framework - Borbon, John Mark Salcedo
The Trends in International Mathematics and Science Study (TIMSS), undertaken by the International Association for the Evaluation of Educational Achievement (IEA), is one of several large-scale assessment studies used to evaluate Grade 4 and Grade 8 learners’ science and mathematics achievement. In TIMSS 2019, the Philippines ranked lowest out of 58 participating countries in the Science 4 assessment with a score of 249. Despite the poor performance of Filipino learners in the said test, extensive analysis of factors affecting their performance has yet to emerge, which this study aimed to provide.